China University Culture - 2008 Contemporary Art Exhibition. (Shanghai : New B Gallery Shanghai, 2008)
Jie, Pu ; Jianjin, Deng ; Zhenhua, Gu ; Jing, Pei ; Wenyu, Ji ; Zhu Weibing ; Li Zhangyang ; Gu Zheng ; Zhao Ping ; Yu Xiaoyu ; Zhao Qin ; Xue Feng ; Jin yangping ; Chen Xiaodan ; Ding Yi ; Jiang Zhenggen ; Wu Wenxing ; Zhou Changjiang ; Tan Genxiong ; Wang Yichu ; Ding She ; Han Feng ; Deng Guoyuan ; Tsai Yulong ; Yuehui, Fu ; Deng Qinghua ; Zhang Yong ; Yanrunan, Tong ; Wang Xiaohui ; Su Xinping
Chinees
Exhibition. China University Culture - 2008 Contemporary Art Exhibition. Shanghai. New B Gallery Shanghai, 16.08.2008 - 26.09.2008.
boek